2019
DOI: 10.5194/wes-2019-88
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differences in damping of edgewise whirl modes operating an upwind turbine in a downwind configuration

Abstract: Abstract. The qualitative changes in damping of the first edgewise modes when an upwind wind turbine is converted into the respective downwind configuration are investigated. A model of a Suzlon S111 2.1 MW turbine is used to show that the interaction of tower torsion and the rotor modes is the main reason for the change in edgewise damping. For the forward whirl mode a maximum decrease in edgewise damping of 39 % is observed and for the backward whirl mode a maximum increase of 18 % in edgewise damping is obs… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
(12 reference statements)
0
2
0
Order By: Relevance
“…In a following study on a 2.1MW turbine Wanke et al (2019b) showed that large downwind cone angles could reduce the edgewise damping further, as the out-of-plane contribution of the edgewise mode shapes is decreased. A significantly reduced tower torsional stiffness, on the other hand, e.g.…”
mentioning
confidence: 95%
“…In a following study on a 2.1MW turbine Wanke et al (2019b) showed that large downwind cone angles could reduce the edgewise damping further, as the out-of-plane contribution of the edgewise mode shapes is decreased. A significantly reduced tower torsional stiffness, on the other hand, e.g.…”
mentioning
confidence: 95%
“…Rotor thrust and tower base fore‐aft moments followed similar trends with lower ultimate loads but additional fatigue wear. Studies also compared the dynamic stability of equivalent upwind and downwind rotors, 23 showing different responses that would justify different design choices, especially in the tower torsional stiffness.…”
Section: Power Production and Loadsmentioning
confidence: 99%